Assembling human Platelet Lysate into multiscale 3D scaffolds for bone tissue engineering - Oliveira, Sara M. (2015)
Scaffolds for bone tissue engineering lack often control of cellular instructions. We propose a triple sequential approach for customizing scaffold features from the macro to the nanoscale. The nano/meso-scale is composed by human platelet lysate and marine-origin polysaccharides assembled by layer-by-layer and shaped into fibrils by freeze-drying. We show that osteogenic induction of stem cells is tunable within a low range of layers. This approach has the potential to develop new scaffolds with enhanced cell-instructive capabilities using affordable autologous sources of bioactive molecules.